Sanghyang Dedari Dance in Geriana Kauh Village, North Duda, Karangasem as the Creation of Painting Works - Arnawa, I Komang Krisna; Mudana, I Wayan; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2023)
Sang Hyang Dedari is a traditional Balinese dance which is interpreted as a ceremonial dance to ask for safety Sang Hyang Dedari is a traditional Balinese dance which and repel reinforcements for the local community. The Sanghyang Dedari dance in Geriana Kauh Village has its own uniqueness, especially in the clothing and attributes used, in the clothing section the yellow and white clothing is used which symbolizes purity and safety or prosperity, which distinguishes Sanghyang in Geriana Village from the Sanghyang in place, namely in terms of the bun or crown, in Geriana Kauh Village they still use natural products as crowns, namely grapefruit peels and flowers such as sandat, cempaka, ratna, gumitir, and jepun flowers, which are arranged in such a way as to resemble a bun. Sanghyang Dedari's performance was performed at the catus pate or crossroad, in the center of the village. Sanghyang Dedari is danced by 2 to 7 child dancers who are underage, not yet mature or mature, these dancers or pengayah have the opportunity to sing for up to 3 terms, after a re-election is held. Sanghyang dedari is accompanied by songs, songs, songs. When dancing, the dancers will follow the strains of the gending being chanted, in the middle of that there is what is called the lilit-linting procession, in which the dancers will climb a bamboo stick and dance to the strains of the gending, this lilit-linting is shaped like a cross or tapak dara, which is also display a safety sign. In this independent project, the author shows the process and sequence of the Sanghyang Dedari dance, from the beginning to the end of the Sanghyang Dedari dance in Geriana Kauh Village, Duda Karangasem Strait.